The most important parasitic diseases in marine cultured fish in Greece - ATHANASSOPOULOU (Φ. ΑΘΑΝΑΣΟΠΟΥΛΟΥ), F. (Journal of the Hellenic Veterinary Medical Society, 2018)
The most important parasitic diseases observed in marine cultured fish in Greece during the period 1995-1999 are described and the aetiological agent, the diagnosis and treatment are summarized.